DAILY VARIATION IN PLASMA-CONCENTRATION OF FENCAMFAMINE AND STRIATAL DOPAMINE-RECEPTORS IN RATS - Planeta, Cleopatra da Silva [UNESP]; Delucia, R.; Aizenstein, M. L.; Oliveira, G. H. (Associação Brasileira de Divulgação Científica (ABRADIC), 1994)
Fencamfamine (FCF) is a psychostimulant drug classified as an indirect dopamine agonist. In the present study we evaluated the daily variation in plasma FCF concentration and in striatal dopamine receptors. Adult male Wistar rats (250-300 g) maintained on a 12-h light/12-h dark cycle (lights on at 07:00 h) were used. Rats received FCF (10.0 mg/kg, ip) at 09:00, 15:00, 21:00 or 03:00 h and blood samples were collected 30 (N = 6) or 60 (N = 6) min after the injections. Plasma FCF was measured by gas chromatography using an electron capture detector. Two-way ANOVA showed significant differences in FCF concentration when blood samples were collected 30 min after the injection, and the highest value was obtained following injection 21:00 h. Moreover, at 15:00, 21:00 and 03:00h, plasma FCF levels were significantly lower 60 min after injection when compared to the 30-min interval. Two other groups of rats (N = 6) were decapitated at 09:00 or 21:00 h and the striata were dissected for the binding assays. The Bmax for [H-3]-spiroperidol binding to striatal membranes was higher at 21:00 h, without changes in affinity constant (Kd). In conclusion, plasma FCF levels and dopamine receptors undergo daily variation,a phenomenon that should be considered to explain the circadian time-dependent effects of FCF.
Keywords: FENCAMFAMINE; DOPAMINE RECEPTORS; CIRCADIAN RHYTHM; CHRONOPHARMACOLOGY; PLASMA FENCAMFAMINE LEVELS